Análise da relação das dimensões comportamentais no contexto do sistema de gestão da qualidade ISO 9000 - Possamai, Luana (My University, 2017)
Several changes have occurred in the area of quality and productivity, especially between the end of the twentieth century and the beginning of the twenty-first century, and some of the main reasons for such changes are related to: competitiveness among organizations at national and international level, the tighteninging of trade barriers, with the creation of large economic blocs; and retraction of world economic growth due to demand from consumers who came to seek products and services with higher quality and lower price. This series of changes made the quality of products and services become essential to the survival of businesses. The adoption of an ISO 9000 Quality Management System (QMS) is an option for companies seeking a differential in the area of quality and recognition through certification. However, the implementation of a quality management system is not a warranty of its success per se, since there must be indeed an internal mobilization and involvement of all organization members with the system. Therefore, to ensure the involvement of all members for this purpose, there must be: internal motivation for quality, the commitment of individuals, knowledge of quality management system combined with the possibility of enriching work, in which the employee can provide ideas and suggestions for improvement. Considering these aspects, the purpose of this study was to analyze the relationship between the constructs: organizational commitment, motivation, organizational learning and empowerment, in the context of ISO 9000 Quality Management System. The quantitative case study, which was carried out through a five-point Likert scale survey, aimed to investigate the perception of employees of company X in relation to constructs and the ISO 9000 Quality Management System in place in the company since the year of 2013. Main results include that the employees have a good perception of the QMS implanted in the company, showing significant difference between the averages by age and tenure. A multiple regression analysis shows that employee perception of QMS is influenced by resource empowerment and motivation due to relationships in the workplace, having a positive correlation with 10 of the 11 factors found in the study.
Várias mudanças ocorreram na área da qualidade e produtividade, principalmente entre o fim do século XX e o início do século XXI, e alguns dos principais motivos que ocasionaram tais alterações dizem respeito a: competitividade existente entre as organizações, não somente a níveis nacionais, mas também internacionais; estreitamento das barreiras comerciais, com a criação de grandes blocos econômicos; retração do crescimento econômico mundial, devido à exigência por parte dos consumidores que passaram a buscar produtos e serviços com maior qualidade e menor preço. Essa série de mudanças fez com que a qualidade de produtos e serviços passasse a ser essencial para a sobrevivência das empresas. A adoção de um Sistema de Gestão da Qualidade ISO 9000 é uma opção para as empresas que buscam um diferencial na área da qualidade e um reconhecimento por meio de certificação. Entretanto, somente a implantação de um sistema de gestão da qualidade não a garante, pois é preciso que exista de fato uma mobilização interna e o envolvimento de todos os membros da organização para com o sistema. Portanto, para garantir o envolvimento de todos os membros é necessário que haja: motivação interna para a qualidade; comprometimento dos indivíduos; e o conhecimento do sistema de gestão da qualidade aliado a possibilidade de um trabalho enriquecedor, em que o colaborador possa dar ideias e sugestões para sua melhoria. Pensando nestes aspectos, este estudo teve como objetivo fazer a análise das relações entre os construtos: comprometimento organizacional, motivação, aprendizagem e empowerment, no contexto do Sistema de Gestão da Qualidade ISO 9000. Por meio do Estudo de Caso de abordagem quantitativa, que se deu por meio da realização de uma survey com escala Likert de cinco pontos, verificou-se a percepção dos funcionários da empresa X com relação aos construtos e o Sistema de Gestão da Qualidade ISO 9000 implementado na empresa desde o ano de 2013. Como principais resultados pode-se verificar que os funcionários possuem uma boa percepção do SGQ implantado na empresa, existindo diferença significativa nas médias por faixa etária e por tempo de serviço. Por meio da análise de regressão verifica-se que a percepção do SGQ sofre influência do empowerment de recurso e da motivação pelos relacionamentos no trabalho, tendo correlação positiva com 10 dos 11 fatores encontrados no estudo.
Keywords: Controle da qualidade - Normas; Comportamento organizacional; Comprometimento organizacional; Aprendizagem organizacional; ISO 9000; Quality control - Standards; Organizational behavior; Organizational commitment; Organizational learning; ISO 9000 Series Standards